Practices That Support and Sustain Health in Schools: An Analysis of SHPPS Data1. (19th February 2019) - Lee, Sarah M.; Miller, Gabrielle F.; Brener, Nancy; Michael, Shannon; Jones, Sherry E.; Leroy, Zanie; Merlo, Caitlin; Robin, Leah; Barrios, Lisa
ABSTRACT: BACKGROUND: The Whole School, Whole Community, Whole Child (WSCC) model provides an organizing framework for schools to develop and implement school health policies, practices, and programs. The purpose of this study was to examine the presence of practices that support school health for each component of the WSCC model in US schools. METHODS: Data from the School Health Policies and Practices Study 2014 were analyzed to determine the percentage of schools with practices in place that support school health for WSCC components. RESULTS: Less than 27% of schools had a school health council that addressed any specific WSCC component, but more than 50% had a coordinator for all but one component. The use of other practices that support school health varied widely across the WSCC components. For example, more than 80% of schools reported family engagement for health education and nutrition environment and services, but less than 50% reported family engagement for other components. CONCLUSIONS: These results indicate that many US schools are using practices that support school health and align with WSCC components, but improvement is needed. These results also highlight discrepancies in the types of practices being used.